Influence of ACTN3 R/X gene polymorphisms on racing strategy in rowing athletes - Miarka, B.; Brito, C. J; Fukuda, D. H.; Castilho Barros, C.; Goulart, C.; Dal Bello, F.; Del Vecchio, F. B. (International Journal of Performance Analysis in Sport, 2017)
This study compared the polymorphisms RR, XX and RX of the ACTN3 gene among rowers with different race strategies across competitive levels and weight categories. We evaluated 137 rowers divided into: male non-elite openweight (n = 23), male elite openweight (n = 33), male non-elite lightweight (n = 31), male elite lightweight (n = 13), female non-elite openweight (n = 9), female elite openweight (n = 9) and female non-elite lightweight (n = 15), female elite lightweight (n = 4). The main results indicated that rowers who adopted starting/early (within the initial 500 m) or finishing/late (within the final 500 m) strategies exhibited similar ACTN3 genotype frequencies, while fewer athletes who adopted moderate (within the middle 1000 m) pacing strategies were categorised with the ACTN3 XX (8%) genotype as compared to the RR (50%) and RX (42%) genotypes (p = 0.002). Elite openweight male rowers with the ACTN3 RR more frequently preferred moderate pacing strategies (p = 0.006), while non-elite lightweight male athletes with ACTN3 RR more frequently preferred starting/early pacing strategies (p = 0.001). Therefore, rowing athletes with specific ACTN3 genotypes may adopt unique race pacing strategies, while no differences were shown by competitive level or weight category.